The Prevalence of Misophonia and Its Relationship with Obsessive-compulsive Disorder, Anxiety, and Depression in Undergraduate Students of Shiraz University of Medical Sciences A Cross-Sectional Study - Yektatalab, Shahrzad (International journal of community based nursing and midwifery, 2022)
Copyright: © International Journal of Community Based Nursing and Midwifery.